Daikibo dēta kanri dēta kanri to katsuyō no tame no modan na dēta ākitekucha patān : dai 2-han / = Data management at scale : - Strengholt, Piethein (Orairī Japan, 2024)
"Data management is subject to disruption. Trends like artificial intelligence, cloudification, ecosystem connectivity, microservices, open data, software as a service, and new software delivery models are causing a paradigm shift in the way data management is practiced. Organizations need to face the fact that decentralization is inevitable. In this practical book, author Piethein Strengholt explains how to establish a future-proof and scalable data management practice. He'll cut through new concepts like data mesh and data fabric and demonstrate what a next-gen data architecture will look like. Executives, architects and engineers, analytics teams, and compliance and governance staff will learn how to shape data management according to their needs. Strengholt provides blueprints, principles, observations, best practices, and patterns to get you up to speed"--
Keywords: Database management; Database design; Electronic data processing -- Management; Information technology -- Management; Bases de données; Gestion; Bases de données; Conception; Technologie de l'information; Gestion